1993
DOI: 10.1017/s0094837300012318
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of sexually dimorphic characters in peccaries (Mammalia, Tayassuidae)

Abstract: Cladistic analysis of osteological and dental characters in a monophyletic group of Miocene and younger tayassuids demonstrates a pattern of changes in the degree of sexual dimorphism in canine tooth diameter and zygomatic arch width, and in phenotypic correlations between these characters. Primitively, tayassuids have canine teeth that are sexually dimorphic and discretely bimodal in size, and zygomatic arches that are narrow in both sexes. Many late Miocene and Pliocene tayassuids have broad, winglike zygoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…This type of response is not supported by the results of the present study, which showed that dimorphism changed even more slowly than predicted by the models. Support for the Lande model of slow SSD evolution (as opposed to the fast response of the sex-limited genes hypothesis) has previously been found in the fossil record: Wright (1993) concluded that skeletal elements of extinct peccaries followed the expectations of the Lande model in that sexually selected structures were found in both sexes before they were slowly reduced in females. In the only other test of the model, Rogers and Mukherjee (1992), analyzing data on the rate of change in dimorphism in three human traits, concluded that the Cheverud mechanism of stronger response in the sex with the higher heritability was not sufficient to account for the existing relationships seen between dimorphism and body size throughout the primate order.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This type of response is not supported by the results of the present study, which showed that dimorphism changed even more slowly than predicted by the models. Support for the Lande model of slow SSD evolution (as opposed to the fast response of the sex-limited genes hypothesis) has previously been found in the fossil record: Wright (1993) concluded that skeletal elements of extinct peccaries followed the expectations of the Lande model in that sexually selected structures were found in both sexes before they were slowly reduced in females. In the only other test of the model, Rogers and Mukherjee (1992), analyzing data on the rate of change in dimorphism in three human traits, concluded that the Cheverud mechanism of stronger response in the sex with the higher heritability was not sufficient to account for the existing relationships seen between dimorphism and body size throughout the primate order.…”
Section: Discussionmentioning
confidence: 84%
“…Although Lande's paper is generally interpreted as predicting that SSD will be slow to evolve (e.g., Rogers and Mukherjee 1992;Wright 1993), this is not a fundamental prediction of the model itself, but rather a consequence of the assumptions made about parameter values. Cheverud et al (1985), again using the standard formulae (eqs 3a,b), showed algebraically that, given assumptions of equal selection intensities and heritabilities in each sex but unequal phenotypic variances, SSD could evolve rapidly and that its magnitude is actually enhanced by high genetic correlations.…”
mentioning
confidence: 99%
“…Thus, assumptions concerning the inheritance of quantitative traits may account for the mediocre predictive power of previous models, even when genetic parameters are accurately estimated (Reeve and Fairbairn 1996). Although sex chromosome mutations and sex-limited mutations on the autosomes (Mackay et al 1992) may allow sexual dimorphism to evolve relatively freely over much longer periods of time (Wright 1993;Fry et al 1995), the rate of such mutations remains virtually unknown. Consequently, the evolution of sexual dimorphism may be constrained, even when the genetic correlation between the sexes is less than perfect.…”
Section: Discussionmentioning
confidence: 99%
“…After some tedious algebra, it was determined that equilibrium allele frequencies are a complex function of sex-specific selection and the presence of other alleles at the same locus (results not shown). Thus, I use Wright's adaptive landscape to illustrate mean population fitness as a function of different patterns of sex-specific selection and different allele frequencies (Wright 1932). I use the product of the sex-specific mean fitnesses (i.e., W ϭ W F ϫ W M ) as the measure of mean population fitness because it is the denominator for all terms on the right hand side of equations (4), (5), and (6).…”
Section: Allele Frequencies In Gametesmentioning
confidence: 99%
“…Based on cranial and dental characters, Wetzel et al (1975) and Wetzel (1977) proposed that Tayassu and Pecari are more closely related to each other than to Catagonus. In contrast, based on his analysis using osteological and dental characters Wright (1989Wright ( , 1993Wright ( , 1998 considered Pecari and Catagonus to be more closely related, whereas Tayassu was considered to be a member of a separate clade along with other extinct species.…”
Section: Acknowledgmentsmentioning
confidence: 99%